Evaluasi Konsistensi Penyajian Laporan Keuangan Terpusat PT. XYZ Di Kota Pekanbaru Sesuai PSAK 65 (Studi : Tanpa Penyajian Terpisah Dari Cabang) - Erna Murniati; Natasha Nadira Putri; Yulia Fitri; Moza Anastasya (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study looks at how consistent PT. XYZ's centralized financial reporting is, as the company doesn't make separate financial reports for its branches, using the rules for consolidation in PSAK 65. The study's goal is to look at how consistent PT. XYZ's financial statements are over time, if they follow PSAK 65, and how this affects the quality of the financial information. We used a qualitative case study method, which included in-depth interviews and document analysis. The results show that the financial reports are consistently made over the years and follow the rules for consolidation, even though reports for each branch are not shown. The centralized method makes reporting more efficient and accurate, but it also makes it less clear and thorough. This study adds to what we know about how companies with non-legal-entity branch structures do centralized reporting.